A Study Of Adjustment Among Secondary School Students In Relation To Their Home Environment - Sathish, kavitha (Journal of Advanced Research in Humanities and Social Sciences; Vol 10 No 2 (2023): Journal of Advanced Research in Humanities and Social Sciences, 2023)
In everyday life, most of the individuals are making adjustment in various activities of their lives. The constant process of adjusting to one's social and physical surroundings is life. The person lives in society and is a part of it from birth.  From the moment of the child's birth until their death, the adjustment process is ongoing. It poses different views depending upon the individual. The concept of adjustment is as old as human race on earth.  Adjustment is the process by which a living organism maintains a balance between its needs and the circumstances that influence he satisfaction of these needs. Man has to constantly make adjustment between his needs and his immediate environment. The adjustment takes place almost in every area of his behavior. Thus adjustment has many dimensions of which the most important are emotional adjustment, social adjustment, and educational adjustment.  Adjustment and adolescence is the two sides of the same coin. Adolescence is the most important period of human life. The years of adolescence are when boys and girls transition physically, cognitively, emotionally, and socially from infancy to maturity. Both boys and girls encounter serious issues during adolescence that are closely tied to their social, mental, emotional, and physical development, among other areas.  A list of 26 questions indicating the significant problems of school students in the three areas were prepared. The tool consists of 30 items to measure the home environment of the school students. The investigator selected a two-point scale in English to measure the sample. The research is to find out the level of Adjustment & Environment among Secondary school students is low and difference between Male and Female Secondary school students based on their Adjustment and Home Environment.  It is found that the level of Adjustment of secondary school students is Moderate in nature and that the level of Home environment of secondary school students is Moderate in nature. It is also found that there exists no significant difference between Male and Female Secondary school students based on their Adjustment and that there exists significant difference between Male and Female Secondary school students based on their Home Environment.